2013
DOI: 10.1590/s0036-46652013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral activity of protease inhibitors against Toxoplasma gondii

Abstract: SUMMARYThe introduction of highly active antiretroviral therapy (HAART) has caused a marked reduction in the occurrence and severity of parasitic infections, including the toxoplasmic encephalitis (TE). These changes have been attributed to the restoration of cellmediated immunity. This study was developed to examine the activity of six antiretroviral protease inhibitors (API) on Toxoplasma gondii tachyzoites. The six API showed anti-Toxoplasma activity, with IC 50 value between 1.4 and 6.6 µg/mL. Further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…falciparum [ 70 ], Leishmania [ 71 ] and T . gondii [ 72 , 73 ]. In addition a native Kunitz-type serine protease inhibitor was recently proven to affect viability of T .…”
Section: Discussionmentioning
confidence: 99%
“…falciparum [ 70 ], Leishmania [ 71 ] and T . gondii [ 72 , 73 ]. In addition a native Kunitz-type serine protease inhibitor was recently proven to affect viability of T .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present investigation, we screened one FDA library comprising 666 small-molecule compounds to identify those that inhibited T. gondii growth. Although we used a known anti-Toxoplasma agent, pyrimethamine, to serve as a positive control, we also noticed that the library contained some established anti-Toxoplasma compounds, such as atazanavir [41], cyclosporine and PHA665752 [28], that, as expected, significantly inhibited T. gondii growth. On the other hand, we found that several compounds, such as SB-408124, semaxanib and U0126, had no effect on T. gondii growth, which is consistent with previous findings [28].…”
Section: Discussionmentioning
confidence: 57%
“…Of the five compounds with the highest inhibitory efficiency (≥ 90% parasite inhibition), three have been reported to inhibit the growth of T. gondii [28,41]. Thus, the remaining two compounds, NVP-AEW541 and GSK-J4 HCl, were further analysed at various concentrations to verify their antiparasitic activity and to determine their therapeutic index (TI).…”
Section: Validation Of the Antiparasitic Activity Of Nvp-aew541 And G...mentioning
confidence: 99%